Effect of seed presoaking in gibberellic acid on cucumber (Cucumis sativus L.) plant growth, flowering, and yield - Al-Sanoussi, A J (Journal of Scientific Agriculture, 2019)
A field experiment was carried out in the region of Sirte, Libya follows completely randomized design with five replicate to evaluate the potential of seed presoaking in different concentrations of gibberellins (0, 5μg/ml, 10 μg/ml and 20μg/ml) on cucumber growth, flowering, and yield. Application of gibberellin (GA3) significantly increased epicotyls length, and plant height (cm) during flowering and at the end of the experimental period compared to the control plants. Moreover, application of GA3 concentration inducing flowering decreased staminate flower number and increased pistillate flower number. Additionally, the promotive effect of GA3 concentration on plant growth and flowering attributes was accompanied by increased yield and its components. The results clearly showed that the foliar application of 10µg/ml GA proved to be the best choice for growing cucumber in terms of growth and yield attributes.